Research of Mobile Internet Core Security Requirement and Protection - Fangheng Xu; Xuan Chen; Cailiang Shen; Huanqiang Du (Dianxin kexue)
Driven by the technology, service and user demand, the mobile internet has enjoyed rapid development in recent years. However, the mobile internet industry of China is still at the initial stage with its form and pattern remains unclear. Based on the development of mobile internet, an overview of the network security problems at current stage was presented, the threats facing mobile internet network were introduced and the relevant ideas and proposals on the security protection were raised.